The convergence and stability of explicit difference schemes for nonlinear schrodinger equation - Ivanauskas, F.; Radžiūnas, M. (Mathematical Modelling and Analysis, 1997)
“The convergence and stability of explicit difference schemes for nonlinear schrodinger equation” Mathematical Modelling Analysis, 2(1), p. 66-74. First Published Online: 14 Oct 2010